2022
DOI: 10.1177/02610183221142216
|View full text |Cite
|
Sign up to set email alerts
|

A critical overview of how English health and social care publications represent autistic adults’ intimate lives

Abstract: Autistic people face more social barriers to, and experience greater anxiety around, intimate relationships than the general population in our majority neurotypical society, leading to increased loneliness and social isolation. National health and social care policies and publications should recognise these inequalities and guide service systems in reducing them. In this paper, we employ a document analysis design to analyse a cross-section of English national health and social care publications to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…A limited number of organisations, mainly within the social care or charitable sector, currently provide education and support with relationships and sexuality for autistic individuals, with hardly any statutory sector provision. Social care staff in England who support autistic adults with sexuality and relationships generally lack sufficient training (Bates et al, 2020), confirmed by a subsequent study (Huysamen et al, 2022). Our participants expressed a strong need for relationships and sexuality support and proposed its inclusion in UK social care assessments, even if immediate assistance is not required.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…A limited number of organisations, mainly within the social care or charitable sector, currently provide education and support with relationships and sexuality for autistic individuals, with hardly any statutory sector provision. Social care staff in England who support autistic adults with sexuality and relationships generally lack sufficient training (Bates et al, 2020), confirmed by a subsequent study (Huysamen et al, 2022). Our participants expressed a strong need for relationships and sexuality support and proposed its inclusion in UK social care assessments, even if immediate assistance is not required.…”
Section: Discussionsupporting
confidence: 56%
“…Participants emphasised the distinctiveness of their needs as autistic people without co-existing learning disabilities and resented being described as "people with learning disabilities and/or autism" which commonly happens in the social care literature (Huysamen et al, 2022). The support participants wanted mirrored the CCF guidance, co-developed with autistic people (Skills for Health, 2019), which is seldom integrated into social care commissioning.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations